Factors Affecting Customer Satisfaction of Mobile Banking Services at Commercial Banks in Nepal - Amit Kumar Sahani (HM Journals, 2024)
Customer satisfaction is an emotion a person experiences when comparing the perceived overall performance of a product to their expectations. Mobile banking has achieved a great importance in Nepal's banking sector. Though majority of Nepalese banks have recognized the importance of understanding customer psychology and are highly conscious of it. The main purpose of this study is to analyze the effect of convenient, communication, time saving, and security of mobile banking in customer satisfaction in commercial banks in Nepal. This research adopts a descriptive and causal comparative research design where in primary data were collected through a survey in the structured questionnaire distributed among a sample of 172 responses was taken from random mobile banking users of different commercial banks which is assumed to comply with the sample size standards for academic research as stated by Hair et al. (2014) which says that the minimum sample for models with up to seven constructs, which is the case of this study as well, must have sample size of 150. The response was taken randomly selected for administration of the questionnaire using the convenience sampling method. This research will be useful to higher management to the banks in developing effective strategies for mobile banking services as well as to retain their customers. Furthermore, Nepal Rastra Bank (Central Bank of Nepal) might be enthusiastic to identify the prevailing problems and technical as well as non-technical barriers concerned with the adoption of the mobile banking on customer satisfaction which will facilitate them to take necessary steps to eradicate barriers and to implement effective policies accordingly.